Sistem Informasi Jasa Laundry Berbasis Website Pada Waroeng Laundry: Website Based Laundry Service Information System at Waroeng Laundry - solihin solihin (Technosience, 2023)
This research “Laundry Services Information System At Waroeng Laundry Website Based”. In the process of writing this research aims to computerize laundry services system by using Website based program, in order to increase the officers performance being more optimal. In addition, the program created can be used to reduce the occurrence of duplication of data and speed up data processing. In conducting this research, the author uses the Waterfall method research. After processing laundry services data and discussing some problems, the author can conclude that the creation of a laundry services information system